Higher Education for Development : An Evaluation of the World Bank Group’s Support - Independent Evaluation Group (World Bank, Washington, DC, 2017)
The World Bank Group’s twin goals have redefined the rationale for engagement across all sectors. Although the World Bank Group has never had an explicit strategy for higher education, institutional- and regional-level strategies and knowledge work anchor the World Bank’s engagement in supporting and promoting (i) greater access and equity, (ii) relevant and quality teaching and research, (iii) improved management and financial systems, and (iv) institutional diversification and innovation.The International Finance Corporation (IFC) has aligned itself with the World Bank’s approach and focuses on access and equity, relevance, and quality. Additionally, IFC has developed a specific education strategy that focuses on its investments in post-secondary education.